Differences in Learning and Inequality* - Ådne Cappelen (Statistics Norway, Research Department, 2006)
Rapid growth in productivity combined with increasing wage dispersion in some countries, notably Anglo-Saxon, has been the subject of numerous studies. The main hypothesis in the literature is that an increased skill premium provides a link between productivity growth and inequality. If this view is correct it poses some challenges for policies that focus on promoting a learning economy. However, data for many OECD-countries show that increased wage dispersion is not a common feature. Many countries have enjoyed a fairly stable or even declining dispersion of wages. Also in countries where the production and use of ITC-goods are significant, there are hardly any changes in wage dispersion. Thus one must look at a broader set of factors other than skilled biased technical change in order to explain the diverse picture of changes in inequality. This paper points to changes in educational attainment and institutions relating to wage bargaining as possible explanations for the varying experience wrt. wage inequality between OECD-countries in recent decades.
Keywords: D31; D33; J31; J50; 330; Inequality; skill premium; bargaining